Adverse vascular remodelling is more sensitive than endothelial dysfunction to hyperglycaemia in diabetic rat mesenteric arteries. (September 2016) - Kahlberg, Nicola; Qin, Cheng Xue; Anthonisz, Jarryd; Jap, Edwina; Ng, Hooi Hooi; Jelinic, Maria; Parry, Laura J.; Kemp-Harper, Barbara K.; Ritchie, Rebecca H.; Leo, Chen Huei
Graphical abstract: Abstract: Increased vascular stiffness and reduced endothelial nitric oxide (NO) bioavailability are characteristic of diabetes. Whether these are evident at a more moderate levels of hyperglycaemia has not been investigated. The objectives of this study were to examine the association between the level of glycaemia and resistance vasculature phenotype, incorporating both arterial stiffness and endothelial function. Diabetes was induced in male Sprague Dawley rats with streptozotocin (STZ; 55 mg/kg i.v.) and followed for 8 weeks. One week post STZ, diabetic rats were allocated to either moderate (⿼20 mM blood glucose, 6⿿7 U/insulin s.c. daily) or severe hyperglycaemia (⿼30 mM blood glucose, 1⿿2 U/insulin s.c. daily as required). At study end, rats were anesthetized, and the mesenteric arcade was collected. Passive mechanical wall properties were assessed by pressure myography. Responses to the endothelium-dependent vasodilator acetylcholine (ACh) were assessed using wire myography. Our results demonstrated for the first time that mesenteric arteries from both moderate and severely hyperglycaemic diabetic rats exhibited outward hypertrophic remodelling and increased axial stiffness compared to arteries from non-diabetic rats. Secondly, mesenteric arteries from severely (⿼30 mM blood glucose), but not moderately hyperglycaemic (⿼20 mM blood glucose) rats exhibit a significant reduction to ACh sensitivity compared to their non-diabetic counterparts. This endothelial dysfunction was associated with significant reduction in endothelium-derived hyperpolarisation and endothelium-dependent NO-mediated relaxation. Interestingly, endothelium-derived nitroxyl (HNO)-mediated relaxation was intact. Therefore, moderate hyperglycaemia is sufficient to induce adverse structural changes in the mesenteric vasculature, but more severe hyperglycaemia is essential to cause endothelial dysfunction.